2021
DOI: 10.1093/cercor/bhab254
|View full text |Cite
|
Sign up to set email alerts
|

Digital Reconstruction of the Neuro-Glia-Vascular Architecture

Abstract: Astrocytes connect the vasculature to neurons mediating the supply of nutrients and biochemicals. They are involved in a growing number of physiological and pathophysiological processes that result from biophysical, physiological, and molecular interactions in this neuro-glia-vascular ensemble (NGV). The lack of a detailed cytoarchitecture severely restricts the understanding of how they support brain function. To address this problem, we used data from multiple sources to create a data-driven digital reconstr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 107 publications
0
47
0
Order By: Relevance
“…Resulting astrocytic meshes were therefore applicable for skeletonization, with which we have successfully developed a novel pipeline to synthesize a digital reconstruction of the NGV ensemble at micrometer anatomical resolution 15 . Moreover, all the resulting meshes were tetrahedralized using T et G en 38 and Gmsh 40 to create corresponding volume, or simulation-ready, meshes for STEPS 31 simulations with which we have successfully completed the objectives of the collaboration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resulting astrocytic meshes were therefore applicable for skeletonization, with which we have successfully developed a novel pipeline to synthesize a digital reconstruction of the NGV ensemble at micrometer anatomical resolution 15 . Moreover, all the resulting meshes were tetrahedralized using T et G en 38 and Gmsh 40 to create corresponding volume, or simulation-ready, meshes for STEPS 31 simulations with which we have successfully completed the objectives of the collaboration.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of representation, processes of astroglial cells are similar to neuronal arborizations, except that they have relatively compact extents and star-shaped structure, and are excessively oversampled in certain cases 15 . Moreover, astrocytic morphologies contain triangular surface patches that represent their endfeet geometries ( Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Cajal already observed a complex arborization using Golgi’s method ( Ramón y Cajal, 1909 ; García-Marín et al, 2007 ). Recent works relying on endogenous sparse labeling techniques ( Hösli et al, 2022 ) and digital reconstructions ( Zisis et al, 2021 ) have revealed the complex three-dimensional structural details of astroglia processes at the vascular but also at the synaptic interfaces ( Torres-Ceja and Olsen, 2022 ). Astrocyte arborization has been underestimated for a long time due to the lack of immunomarkers labeling not only main processes, as shown with GFAP, S100β, or Aldh1l1 staining, but also fine branches.…”
Section: Astrocyte Maturationmentioning
confidence: 99%
“…Accumulating evidence supports that astrocyte undergoes significant changes after the stroke in morphology, gene expression, and cell proliferation, and these cells are known as RAs ( Zisis et al, 2021 ). Currently, it is known that the RAs’ effects may include scarring, neurotrophic factor secretion, BBB damaging and repairing, and inhibition of synaptic formation.…”
Section: Introductionmentioning
confidence: 99%